Municipal executive recommendation by citizens: Who is most significant? - Galv\~ao Meirinhos; Maximino Bessa; Carmem Pereira Leal; Márcio José Sol Pereira Oliveira; Amélia Carvalho; Rui Silva (Administrative Sciences, 2022)
This paper explores which variables are more significant in municipal executive recommendation by citizens. We estimated the influence of public dimensions, such as municipe loyalty, municipe satisfaction, and municipe perceived value in municipal executive recommendation by citizens. Then, we tried to understand if the citizen's opinions influenced the evaluation of the municipal executive recommendation. The parishes of the municipality of Valongo were selected and analyzed, namely the parishes of Alfena, Campo e Sobrado, Valongo, and Ermesinde, and a total of 998 questionnaires were collected. Data were collected in November 2020 in the different parishes under study. It was concluded that all studied dimensions were statistically significant in the final structural estimated model. The structural results point to municipe loyalty and municipe satisfaction dimensions having a direct, positive, and statistically significant influence on municipal executive recommendation. On the other side, the municipe perceived value dimension has a direct positive but not statistically significant influence on municipal executive recommendation. This study showed that a loyal and satisfied citizen recommends the continuity of the municipal executive in the city's political leadership in which he or she lives. Therefore, for the municipal executive administration, it is fundamental to know which dimensions the society considers most important in order to be able to remain in the management of the shared destinies of a city. In this sense, political decisions throughout the mandates can be directed, on the one hand, to the satisfaction and loyalty of the citizens and, on the other hand, to the balanced management of the destinies of this type of public entity.
Keywords: 350; municipal executive recommendation; municipe loyalty; municipe perceived value; municipe satisfaction